Evaluasi Workshop Bahasa Inggris Berbasis Analisis Kebutuhan bagi Guru Pendidikan Anak Usia Dini - Budianto, Martha (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
This study aims to evaluate the implementation and impact of an English training workshop for early childhood education teachers in Surakarta. The study employed a program evaluation design using a qualitative descriptive approach involving twenty playgroup and kindergarten teachers. The workshop was conducted over four days and was designed based on a needs analysis obtained through a pre-test and preliminary interviews. Data were collected through pre-test and post-test results, reflective questionnaires, and semi-structured interviews. The qualitative data were analyzed using thematic analysis. The findings indicate that the workshop had a positive impact on participants’ English proficiency as well as their affective aspects, particularly their confidence in using English in the classroom. The thematic analysis identified three main themes: emotional responses, understanding of the material, and collaboration. Participants demonstrated increased enthusiasm, reduced anxiety, and improved self-confidence. Contextual and practical materials helped participants connect theoretical concepts with classroom practice. Furthermore, interactive activities and collaborative discussions strengthened professional engagement and peer learning. These findings confirm that structured and needs-based training is effective in supporting the sustainable professional development of early childhood education teachers and contributes to improving the quality of English instruction in the classroom.